Combined Perilunate and Axial Ulnar Dislocation of the Wrist - Gvozdenovic, Robert; Nielsen, Niels Søe; Garcia-Elias, Marc (Journal of Wrist Surgery, 2012)
Carpal axial injuries are rare and devastating and can be difficult to classify because of various possible injury combinations. A 54-year-old man was involved in a road accident, resulting in serious injury to his dominant right wrist. An axial injury between the capitate and the hamate was combined with open perilunate dislocation and fracture, metacarpal II and III dislocation, and radial styloid fracture. This specific carpal injury has not been previously described. Our clinical case description will contribute to the understanding of the mechanism and pathology of axial carpal injuries. Proximal row carpectomy and pinning-fixation yielded good result at 3 years follow-up. We posit that these rare axial carpal injuries combined with some stage of perilunar injury can be considered a specific injury type in the classification of axial carpal injuries.
Keywords: axial carpal injury; capitohamate injury; perilunar injury; lunate fracture; axial dissociation